Implementation of Administrative Law in Local Government Policy: An Empirical Qualitative Study Using NVivo - Muhammad, Mukmin (LPPPIPublishing, 2026)
This study examines the implementation of administrative law in local government policy through an empirical qualitative approach assisted by NVivo software. Administrative law serves as a fundamental framework for guiding public administration, ensuring accountability, transparency, and legal certainty, particularly in decentralized governance contexts. Despite comprehensive regulatory arrangements, local governments often face challenges in translating administrative law principles into effective policy implementation. This research aims to explore how administrative law is interpreted and applied by public officials in real policy settings. Data were collected through in-depth semi-structured interviews, field observations, and document analysis involving local government officials, legal officers, policy implementers, and community representatives. The qualitative data were analyzed using NVivo through open, axial, and selective coding processes to identify recurring patterns and key themes. The findings reveal that while administrative law principles are formally acknowledged, their implementation is frequently hindered by institutional limitations, discretionary practices, and weak oversight mechanisms. The study provides empirical insights into administrative law practices and offers policy-relevant recommendations for strengthening governance and administrative accountability at the local government level.